2007
DOI: 10.1192/pb.bp.106.011577
|View full text |Cite
|
Sign up to set email alerts
|

Crime rates and local newspaper coverage of schizophrenia

Abstract: Aims and MethodThe association in the media of mental illness with violence is well established. This study looks at whether there are differences in the portrayal of schizophrenia in the local newspapers of Nottingham, an area with a high crime rate and Dorset, an area with a low crime rate.ResultsWe analysed 98 newspaper articles, 55 from Nottingham and 43 from Dorset, and found no statistically significant difference in the portrayal of schizophrenia. Overall, 36.1% of articles were negative in tone, 56.7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…In the United Kingdom, Chopra & Doody (2007) found that local newspaper articles referring to schizophrenia had a negative tone five times as often as a positive tone, and most of the negatively toned articles related to crime and violence. Also in the UK, Goulden et al, (2011) found that 68% of recent stories about schizophrenia mentioned "bad news", primarily involving dangerousness, a much higher rate than for any other psychiatric condition.…”
mentioning
confidence: 98%
“…In the United Kingdom, Chopra & Doody (2007) found that local newspaper articles referring to schizophrenia had a negative tone five times as often as a positive tone, and most of the negatively toned articles related to crime and violence. Also in the UK, Goulden et al, (2011) found that 68% of recent stories about schizophrenia mentioned "bad news", primarily involving dangerousness, a much higher rate than for any other psychiatric condition.…”
mentioning
confidence: 98%
“…Mental illness stigma consists of negative attitudes (i.e., prejudices), beliefs (i.e., stereotypes), and behaviors (i.e., discrimination; Link & Phelan, 2001; Rüsch, Angermeyer, & Corrigan, 2005) toward people with mental illness. Stigma is prevalent, both among the general public and those with mental health training (Kingdon, Sharma, & Hart, 2004; Lyons & Ziviani, 1995; Parcesepe & Cabassa, 2013), is often perpetuated through the media (Chopra & Doody, 2007), and has persisted over the past several decades at a consistent rate (Rüsch et al, 2005; Vahabzadeh, Wittenauer, & Carr, 2011). One consequence of public stigma is the self-stigma that can result among those with mental illness, where negative beliefs and attitudes about symptoms or recovery are internalized (Corrigan & O’Shaughnessy, 2007).…”
mentioning
confidence: 99%
“…An assumption was made that students' prior knowledge was comparable to a member of the public's and therefore likely to be influenced by popular media portrayals of mental illness 7 or personal experience involving themselves, friends or relatives.…”
Section: Course Structure and Materialsmentioning
confidence: 99%